Does age determine the lightness and darkness of tooth shades? A retrospective study - Revathi Bhaskaran; Subash Sharma (Wolters Kluwer Medknow Publications, 2022)
The study aimed to analyze whether age determines the lightness and darkness of tooth shades. The demand for esthetics has soared to a next level progressively in many developing countries including India; the importance provided to match the tooth shade creates a great difference in the satisfactory outcome of the patient in the field of dentistry. Therefore, this particular study analyzed the differences in tooth shade values based on age factor among the Indian population. 238 individual's case sheets with the age between 18 and 65 years. 18-30 years of age were considered as group 1 (young adults), 31-45 years in group 2 (middle age), and above 45 years in group 3 (older age). The clinical intraoral pictures of the patients which were taken prior to the treatment were obtained and the shade of any one of the upper permanent central incisors was assessed using the Vitapan 3D-Master shade guide, especially the middle portion of the facial surface of the incisors. The collected data were imported to Statistical Package for the Social Sciences, version 17 (IBM Corporation). Chi-square test was used to assess the significance. From the data, 17.2% showed A1 shade, 35.2% A2 shade, 7.5% A3 shade, 5% A4 shade, 7.1% B1 shade, 15.9% B2 shade, 7.1% B3 shade, 3.3% B4 shade, and 1.1% C1 shade. The individuals under the category of above 45 years showed darker tooth shade compared to young adults and middle age population (Chi-square test, P < 0.001). Significant association was established with darker tooth shades by increasing age and vice versa. The older age population showed a higher correlation for dark shade between teeth. The aging process significantly affects the teeth color. Hence, as a dentist, it is important to know about the distribution of tooth shade and its association with age to get an outcome with adequate patient satisfaction.